Mo modified Co3O4 nanosheets array by a rapid quenching strategy for efficient oxygen evolution electrocatalysis - Yang, Jiangping; Zhang, Zhe; Sun, Siyuan; Wang, Cheng (Frontiers in Materials, 2022)
The development of transition metal oxides (TMOs) as electrocatalysts for oxygen evolution reaction (OER) has the potential to surpass the performance of noble-metal-based catalysts. In this work, a quenching rapidly strategy was used to synthesize Mo-modified Co3O4 nanosheet arrays as advanced catalysts. The resulting Mo-Co3O4 electrodes showed superior activity and reaction kinetics, with an overpotential of only 341 mV to drive a current density of 100 mA cm−2 and a Tafel slope of 69.0 mV dec−1. This improved performance is thought to be due to the formation of high-valence Co sites, which creates a synergistic effect. The ability to regulate the synthesis without causing obvious agglomeration and nucleation growth during annealing makes this method a promising approach for the design of other advanced functional materials.